Integration of Islamic Educational Values on the “Kampus Mengajar” Program in Makassar - Haeriyyah, Haeriyyah; Agussalim, Andi; Mujahid, Ahmad; Anwar, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study examines how Islamic educational values are integrated into the Kampus Mengajar Program at elementary schools in Makassar and how this integration contributes to students’ character development in the face of global and moral challenges. Using a qualitative case study approach, data were collected through observations, interviews, and document analysis in five elementary schools participating in the program across Makassar. The research involved 12 informants, including Kampus Mengajar participants from Universitas Hasanuddin and the elementary school teachers they collaborated. The collected data were analyzed using Miles and Huberman's interactive analysis model, which includes data reduction, data display, and conclusion drawing. The study found that integrating Islamic educational values, such as Tauhid, akhlak, ibadah, and muamalah, into classroom activities significantly enhanced students' character development, particularly regarding honesty, responsibility, and tolerance. These values were instilled through religious rituals, community projects, and everyday interactions. The program also fostered students' awareness of environmental ethics and social empathy. The findings suggest that Kampus Mengajar is an effective vehicle for character education aligned with Islamic values. It is recommended that future implementations provide structured training for participants on Islamic educational integration. Further research could examine the long-term behavioral impacts on students and the institutional sustainability of such value-based educational programs.